The Term depression in Contemporary Lithuanian Journalism - Zemlevičiūtė, Palmira (Verbum, 2023)
The article attempts to look into the ways that the special meaning of the term depression (Lith. depresija) changes in the discourse of journalism and the factors that drive those changes. Analysis of nearly 2,000 sentences featured in the Corpus of the Contemporary Lithuanian Language that contain the term depression has shown that only one meaning of this term (medical) undergoes transformation as the term transcends the boundaries of a special field, while the rest of its meanings are not susceptible to change. First, the terminological meanings in which this term is used in the material covered by the analysis basically do not change at all, and no break between the term and the underlying concept occurs. Second, the terminological (medical) meaning changes to an extent, and the concept becomes simplified. Third, the terminological meaning undergoes a series of different semantic transformations and the term becomes even more detached from the special meaning, acquiring a number of emotional, expressive shades. These transformations depend on the topics covered by texts, the intentions of the authors, the contextual partners (adjectives, verbs), which often carry some stylistic connotations. Still, it can be sometimes difficult to determine the extent of transformation of the terminological meaning of the term depression with a high degree of accuracy. At times, the boundary between the term depression and the word depression becomes unclear.
Keywords: term; meaning; determinologisation; journalism